Lessons learnt from assessing and improving accuracy and positive predictive value of the national HIV testing algorithm in Nigeria - Augustine O. Mpamugo; Nnaemeka C. Iriemenam; Adebobola Bashorun; Olumide O. Okunoye; Orji O. Bassey; Edewede Onokevbagbe; Tapdiyel Jelpe; Matthias A. Alagi; Chidozie Meribe; Rose E. Aguolu; Charles E. Nzelu; Segun Bello; et al. (African Journal of Laboratory Medicine, 2024)
Background: HIV testing remains an entry point into HIV care and treatment services. In 2007, Nigeria adopted and implemented a two-test rapid HIV testing algorithm of three HIV rapid test kits, following the sequence: Alere Determine (first test), UnigoldTM (second test), and STAT-PAK® as the tie-breaker. Sub-analysis of the 2018 Nigeria HIV/AIDS Indicator and Impact Survey data showed significant discordance between the first and second tests, necessitating an evaluation of the algorithm. This manuscript highlights lessons learnt from that evaluation.